Enriquecimento do âmnio com treonina em embriões de frangos corte: 1. Desempenho e morfofisiolgia intestinal e 2. Efeito sobre a contagem de Salmonella Enteritidis e microbiota cecal - Moreira Filho, Alexandre Lemos de Barros (2017)
The phase after hatching is determinant in the life of the chick, during which crucial transformations occur to guarantee survival. The rapid development of the gastrointestinal tract to assure the assimilation of nutrients is one of the most important. At hatching, the chick is exposed to several types of microorganisms and defense mechanisms are still underdeveloped. Feeding of nutrients involved in intestinal immune response may be a viable alternative in improving the response of chicks to pathogens. In ovo supplementation of threonine during embryogenesis was studied as well as its effect on the development of the intestinal mucosa, expression of intestinal genes and cecal microbiota in response to challenge with Salmonella. In Chapter II, the effect of threonine levels (0.0; 1.75; 3.5; 5.25; 7.0%) provided in ovo was assessed by chick performance and the expression of mucin (MUC2), peptide transporter (PepT1), and aminopeptidase enzyme (AP) genes in the jejunum. In ovo threonine supplementation significantly increased (p <0.001) the final weight, weight gain, and reduced feed conversion over the 1 to 21 day period. Threonine levels beneficially affected villus height, villus: crypt ratio and villous area. On the day of hatching all threonine levels supplemented in ovo increased expression of MUC2, PepT1 and AP; it is worth noting that AP expression in the lowest and highest level of supplementation (1.75 and 7.0%) was similar to that of the control treatment. No significant effects were observed for MUC2, PepT1 and AP expression at 21 days of age. In Chapter III, the effect of in ovo Threonine supplementation on the response of broilers challenged with Salmonella Enteritidis in the post-hatching phase was evaluated, considering the cecal bacterial count, intestinal morphology, final weight and weight gain in different periods post-challenge with Salmonella. Threonine supplementation in ovo at 3.5% reduced Salmonella Enteritidis counts in the cecum at 168-hour post inoculation (hpi). In addition, threonine supplementation improved the intestinal mucosa development and performance in broilers in the initial phase. In Chapter IV, data are presented on the evaluation of the effect of in ovo threonine on the diversity and composition of the cecal microbiota in different periods of chicks submitted to challenge with Salmonella Enteritidis. At hatching, diversity is limited and the populations consist mainly of bacteria of the phylum Proteobacteria. The diversity increases with age and the microbiota composition is shifted to a greater proportion of bacteria belonging to Firmicutes phylum. The challenge with Salmonella did not change the cecal microbiota diversity and composition. In ovo threonine supplementation altered the diversity and composition of the microbiota in the period of 96 hours after the challenge, favoring the establishment of bacteria of the family Lachnospiraceae. In conclusion, the in ovo threonine supplementation beneficially affected the morphological and functional development of the intestinal mucosa and promoted changes in the intestinal microbiota, favoring the establishment of the commensal microbiota, promoting improvements in the intestinal health of broilers challenged with Salmonella Enteritidis.